Women's empowerment, work environment, and income: evidence from India. Issue 4 (19th May 2022) - De, Indranil
ABSTRACT: This study focuses on the implications of various work environments on women's empowerment based on a survey of women employed in various occupations in a remote urban area. The results reveal that women employed in employer's enterprise outside the employer's dwelling are more likely to make or influence financial and non-financial decisions within the household. These women are also more likely to influence social decisions outside the household. Women engaged with home-based traditional industries are less likely to influence decisions. Women associated with SHG, trust, voluntary organisations, or federations more likely to make or influence decisions. Access to alternative employment has a positive association with decision-making. Women employed in employer's enterprise outside the employer's dwelling and women not having any specific workplace are more likely to consider a different profession for their daughters.